A review of vedolizumab and ustekinumab for the treatment of inflammatory bowel diseases. Issue 5 (20th June 2018) - Shim, Hang Hock; Chan, Pak Wo; Chuah, Sai Wei; Schwender, Brian J; Kong, San Choon; Ling, Khoon Lin
Abstract : Recent advancement in the understanding of the pathophysiology of inflammatory bowel disease has seen an expansion in therapeutic options. Vedolizumab, a selective α4β7 inhibitor, and ustekinumab, an IL 12/23 p40 inhibitor, have provided the much‐awaited out‐of‐class alternatives for patients who have failed or who are intolerant to anti‐Tumor Necrosis Factor (TNF) therapy. However, questions remain as to how we may best use these novel therapeutic agents. We evaluate the evidence available from randomized controlled trials and postmarketing cohort studies and discuss their safety, efficacy, and limitations, in relation to anti‐TNF therapy, in optimizing the treatment outcomes. Abstract : Recent advancement in the understanding of the pathophysiology of inflammatory bowel disease has seen an expansion in the therapeutic options. We evaluate the evidence available from randomized controlled trials and post‐marketing cohort studies for vedolizumab and ustekinumab, and discuss their safety, efficacy and limitations in relation to anti‐TNF therapy in optimizing the treatment outcomes.